Особливості формування маркетингових трендів - Бєлова, Тетяна Геннадіївна; Дунін, Максим Євгенович (My University, 2021)
Стаття присвячена особливостям формування маркетингових трендів. Доводиться необхідність вивчення тренду як явища. Наводяться визначення поняття «тренд» різними авторами. Підкреслюється багатогранність проблеми, яка розглядається. Наводяться види маркетингових трендів, які мають прояв на світовому рівні. Окреслюються особливості формування та розвитку українських трендів. Вивчаються маркетингові тренди, які притаманні пивоварній галузі України як типового представника галузевого ринку. The article is devoted to the peculiarities of the formation of marketing trends. The need to study the trend as a phenomenon is proved. Definitions of the concept of "trend" by different authors are given. The versatility of the problem under consideration is emphasized. The types of marketing trends that are manifested at the global level are given. Peculiarities of formation and development of Ukrainian trends are outlined. Marketing trends that are inherent in the brewing industry of Ukraine as a typical representative of the industry market are studied.
Keywords: Digital-маркетинг; маркетинговий тренд; світовий тренд; креативність; marketing trend; global trend; digital marketing; creativity; кафедра маркетингу